Ultrahypofractionated Proton Radiation Therapy in the Treatment of Low and Intermediate-Risk Prostate Cancer-5-Year Outcomes - Kubeš, Jiří; Haas, Alexandra; Vondráček, Vladimír; Andrlík, Michal; Navrátil, Matěj; Sláviková, Silvia; Vítek, Pavel; Dědečková, Kateřina; Prausová, Jana; Ondrová, Barbora; Vinakurau, Štěpán; Grebenyuk, Alexander; et al. (International journal of radiation oncology, biology, physics, 2021)
PURPOSE: To analyze the 5-year biochemical disease-free survival (bDFS) and late toxicity profile in patients with prostate cancer treated with pencil beam scanning (PBS) proton radiation therapy. METHODS AND MATERIALS: Between January 2013 and March 2016, 284 patients with prostate cancer were treated using intensity modulated proton therapy (IMPT), with an ultrahypofractionated schedule (36.25 GyE in 5 fractions). Five patients were immediately lost from follow-up and thus were excluded from analysis. Data for 279 patients were prospectively collected and analyzed with a median follow-up time of 56.5 (range, 3.4-87.5) months. The mean age at time of treatment was 64.5 (40.1-85.7) years, and the median prostate-specific antigen (PSA) value was 6.35 μg/L (0.67-17.3 μg/L). A total of 121 (43.4%) patients had low-risk, 125 patients (44.8%) had favorable, and 33 (11.8%) unfavorable intermediate-risk cancer. In addition, 49 (17.6%) patients underwent neoadjuvant hormonal therapy, and no patients had adjuvant hormonal therapy. bDFS and late toxicity profiles were evaluated. RESULTS: The median treatment time was 9 days (range, 7-18 days). The 5-year bDFS was 96.9%, 91.7%, and 83.5% for the low-, favorable, and unfavorable intermediate-risk group, respectively. Late toxicity (Common Terminology Criteria for Adverse Events v.4) was as follows: gastrointestinal: grade 1, 62 patients (22%), grade 2, 20 patients (7.2%), and grade 3, 1 patient (0.36%); genitourinary: grade 1, 80 patients (28.7%), grade 2, 14 patients (5%), and grade 3, 0 patients. PSA relapse was observed in 17 patients (6.1%), and lymph node or bone recurrence was detected in 11 patients. Four (1.4%) local recurrences were detected. Nine patients (3.2%) died of causes unrelated to prostate cancer. No deaths related to prostate cancer were reported. CONCLUSION: Ultrahypofractionated proton beam radiation therapy for prostate cancer is effective with long-term bDFS comparable with other fractionation schedules and with minimal serious long-term GI and GU toxicity.
Keywords: výsledek terapie; nádorové supresorové proteiny; přežití bez známek nemoci; lidé; protonová terapie; membránové proteiny; Radiation Dose Hypofractionation; nádory prostaty; Treatment Outcome; Prostatic Neoplasms; Male; Tumor Suppressor Proteins; Aged; Membrane Proteins; Disease-Free Survival; hypofrakcionace při ozařování; lidé středního věku; senioři; mužské pohlaví; Proton Therapy; Middle Aged; Humans